Gastric Volvulus in Association with Bockdalekhernia in Adult Patient (Case Report) - Al-Khazraji, Zakaria Yahia Al-Khazraji; Ali, Hiba A.; Mohammed Zahed Abdul Razaq; Ahmed, Mustafa Abdul Karim; Abeer Nibras Nimr; Fadhi, Hussein Alaa-alden (American Journal of Health, Medicine and Nursing Practice, 2024)
Purpose: Bochdalek hernia (BH) in adulthood is rare. Symptomatic BH in adults is rarer, but may lead to fatal complications. Patients with acute gastric volvulus on diaphragmatic hernia are a diagnostic and therapeutic emergency. Materials and Methods: A 22-year-old male patient presented to our emergency department with a two-day history of severe epigastric pain. The pain was dull in nature with dyspnea on lying supine. Findings: The stomach was within the thorax on the left side due to left diaphragmatic hernia of a nontraumatic cause, diagnosed by chest radiograph, and computed tomography (CT). The patient was prepared for the open surgical repair, to close the defect. The patient recovered with accepted general condition and was discharged 5 days later. In conclusion, in our case, we report this rare presentation of BH with gastric volvulus as an urgent condition that needs to be diagnosed as early as possible to prevent fatal complications. Implications to Theory, Practice and Policy: A diagnosis of an adult diaphragmatic hernia should always be kept in mind in patients with overlapping abdominal and respiratory symptoms with or without a history of trauma.